PENGARUH DESAIN KEMASAN PRODUK DAN DAYA TARIK IKLANTERHADAP KEPUTUSAN PEMBELIAN YANG DIMEDIASI OLEHKESADARAN MEREK PRODUK AIR MINUM CLEODI KABUPATEN MOJOKERTO - Khoirul Umam; Dedeh Imam Fatmasari; Ali Anwar (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2021)
This study aims to find out the Influence of Product Packaging Design and AdvertisingAttractiveness on Purchasing Decisions Mediated by Cleo Drinking Water Product BrandAwareness in Banda Aceh City. The technique used in the study for sampling is nonprobability sampling, with a sample count of 207 respondents. The equipment in the datacollection in this study used questionnairesthat were distributed directly to the people ofBanda Aceh. In this study, researchers used the StructuralEquation Modeling (SEM) methodas an analysis method to see the influence of all the variables involved. Based on the resultsof the hypothesis, itstatesthat Product Packaging Design has a significanteffect on purchasingdecisions. The attractiveness of advertising has a significant effect on purchasing decisions.Product packaging design has a significant effect on brand awareness. The attractiveness ofadvertising has a significant effect on brand awareness. Brand awareness has a significanteffect on purchasing decisions. Brand awareness is able to mediate product packaging designon purchasing decisions. Brand awareness is able to mediate the attractiveness of advertisingon purchasing decisions.